An Exploratory Study of the Impact of Gender on Health Behavior Among African American and Latino Men With Type 2 Diabetes. (March 2017) - Hawkins, Jaclynn; Watkins, Daphne C.; Kieffer, Edith; Spencer, Michael; Piatt, Gretchen; Nicklett, Emily J.; Lebron, Alana; Espitia, Nicolaus; Palmisano, Gloria
This study explores gender values and beliefs among Latino and African American men with diabetes and examines how these values and beliefs may influence their health behaviors. Participants were recruited from individuals who participated in one of three Racial and Ethnic Approaches to Community Health Detroit Partnership diabetes self-management interventions. One focus group was conducted with African American men ( n = 10) and two focus groups were conducted with Latino men ( n = 12) over a 3-month period. Sessions lasted 90 minutes, were audiotaped, and analyzed using thematic content analysis techniques. Two themes emerged that characterize gender identity and its relationship to health behavior in men: (a) men's beliefs about being men (i.e., key aspects of being a man including having respect for themselves, authority figures, and peers; fulfilling the role as breadwinner; being responsible for serving as the leader of the family; and maintaining a sense of chivalry) and (b) influence of gender values and beliefs on health behavior (i.e., the need to maintain a strong image to the outside world, and the need to maintain control of themselves served as barriers to seeking out and engaging in diabetes self-management behaviors). Results suggest that gender values and beliefs may have implications for how health behaviors among men with diabetes. Future research should study the direct impact masculine identity has on health behaviors among men with diabetes.